Effect of Interaction of Various Nitrogenous and Ligno-cellulosic Amendments on Biomass Production of Pleurotus Florida - Ghosh, Payal; Biswas, Mohan (International Journal of Bio-resource and Stress Management, 2023)
Pleurotus florida, commonly known as oyster mushroom, grows easily on various agricultural wastes, having high content of protein which contains essential amino acids. This study was carried out to determine the optimal parameters for the production of P. florida in lateritic zone of West Bengal State in India under uncontrolled environmental condition. Among all the nitrogenous supplementation, saw dust showed maximum bio-efficiency followed by rice bran. Among the interaction study of various oil types, maximum yield on coconut oil followed by sunflower oil amendment was obtained.